How operational performance impacts customer retention : insights from retail data - Ribeiro, Eduardo Manuel da Graça Jorge da Silva (2019)
In recent years, online business has grown to account for 10.2% of sales in the retail industry. In this study, I look at how consumers react to operational performance or under-performance when purchasing online, and how this relates to customer retention. The operational performance is measured as the retailer´s ability to deliver the exact kind and amount of products chosen by their consumers (PickingSuccess). I begin with standard regression techniques, which are applied to assess the influence of performance on retention, and find that customer retention is positively related to good operational service. I then proceed with a causal method, where I divide customers into two groups, those that received above-average and below-average customer service, resulting from better and worse operational performance. Matching each customer in the below average bracket with their counterparts in the above average bracket according to customer characteristics (basket size, total amount spent, etc), allows us to reduce selection bias. The resulting regression analysis tells us that customers with above average service ordered 137% more often than their counterparts. I also find that the first interaction between retailers and customers is the most important: Customers who get what they want the first time are 17% more likely to purchase again, than those who leave the retailer “unsatisfied”. We conclude that a strategy recognizing the importance of customer service, especially for new clients, yields a better retention rate.